The utility of simplified quantification of training: The training of a Japanese national canoe sprint team for the London Olympic Games - Nakagaki, K.; Onoto, N. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
The purpose of this study was to evaluate the utility of simplified quantification of training in for a Japanese national canoe sprint team using the modified session rating of perceived exertion method. We recorded the team's training using a method that integrates the original weighting factor (WF) and the duration (time) of the training session. Training load was quantified as the product of WF and time. Training monotony was calculated by as the mean daily load divided to the standard deviation of load. Training strain was calculated by multiplying the weekly training load by training monotony. A fitness-fatigue model was applied to the relationships between training load and performance. The model-predicted performance using the training load was significantly correlated with actual paddling performance. The training load and strain were significantly correlated with resting heart rate in the early morning. These results suggest that simplified quantification of training can be used to prescribe training for the improvement of performance and the prevention of overtraining syndrome.